Valoración de Mezclas Asfálticas Fabricadas en Planta y en Caliente con Asfaltos Modificados con Látex UP70 SBR - Fernández-Calvo, Rodrigo Ariel (Instituto Tecnológico de Costa Rica, 2006)
The actual condition in which the principal roads of the country are, has taken the public works autorithies to take action so that they can correct and avoid those inconvenients on the future road works. That`s why during the construction of the improvement of the 23 national road, Interamericana-Caldera section, the inclusion of polimers in the asphaltic mix to be placed in the construction was established. Taking advantageof this situation it was proceeded to colect the design and production data ,rehearsed by the involved labs in the process, to be able to value the behavior of one asphaltic mix fabricated in its plant and in hot, modified with latex UP70SBR. This valoration was done through the diametral tension and retained resistance results, wich allowed to conclude that the polimer influences favorably in its durability. The process of colocation was visualized and documented, which allowed to reflect a series of differences in the behavior of the modified mix in comparison to a virgin mix like the little energy thats needed to give the required compactation grade and the shown lost of workability.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2006.
Keywords: Plastómeros; Dosificación; Módulo Resilente; Compactación; Vías públicas